1996
DOI: 10.1093/carcin/17.4.767
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to dimethylarsinic acid, a main metabolite of inorganic arsenics, strongly promotes tumorigenesis initiated by 4-nitroquinoline 1-oxide in the lungs of mice

Abstract: The effect of dimethylarsenics on the pulmonary tumorigenesis initiated by 4-nitroquinoline 1-oxide (4NQO) in mice was examined. The exposure of mice to dimethylarsinic acid (DMAA), a major metabolite of inorganic arsenics in mammals, resulted in not only promotion but also progression of the tumorigenic process in the lungs of mice administered 4NQO. Furthermore, dimethylarsenics influenced the differentiation process in lung tumorigenesis by 4NQO. These results may pave the way for the elucidation of lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
53
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 16 publications
0
53
0
Order By: Relevance
“…26,27) We have estimated that the promotion and progression of lung-and skin-tumorigenesis in mice is not directly ascribable to DMA itself, but to the dimethylarsenic peroxy radical [(CH 3 ) 2 AsOO ·] 15) produced during the metabolic processing of DMA. [5][6][7] This is a reactive oxygen species (ROS). There are two reports showing the positive data of 8-hydroxy-2Ј-deoxyguanosine (8-OHdG), known as a product of oxidative damage due to ROS, by arsenic exposure: One demonstrated the enhancement of the amount of 8-OHdG in the liver of rat by DMA exposure, 12) and another provided 8-OHdG positive data in arsenic-related neoplasms and keratoses of humans.…”
Section: Increase In 8-ohdg In Urinementioning
confidence: 99%
See 4 more Smart Citations
“…26,27) We have estimated that the promotion and progression of lung-and skin-tumorigenesis in mice is not directly ascribable to DMA itself, but to the dimethylarsenic peroxy radical [(CH 3 ) 2 AsOO ·] 15) produced during the metabolic processing of DMA. [5][6][7] This is a reactive oxygen species (ROS). There are two reports showing the positive data of 8-hydroxy-2Ј-deoxyguanosine (8-OHdG), known as a product of oxidative damage due to ROS, by arsenic exposure: One demonstrated the enhancement of the amount of 8-OHdG in the liver of rat by DMA exposure, 12) and another provided 8-OHdG positive data in arsenic-related neoplasms and keratoses of humans.…”
Section: Increase In 8-ohdg In Urinementioning
confidence: 99%
“…On the other hand, some reports indicated that DMA exposure in rats increased the activity of ornithine decarboxylase (ODC), a tumor promotion marker, in the liver 9,12) ; conversely, DMA exposure in mice decreased that in the liver and lung, 28) although DMA administration promoted lung-and skin-tumorigenesis. [5][6][7][8][9] These facts suggest that rats are more responsive to dimethylarsenic than mice in terms of tumor promotion.…”
Section: Increase In 8-ohdg In Urinementioning
confidence: 99%
See 3 more Smart Citations